Single Nucleotide Polymorphism Profiles of Patients with Acute Renal Rejection to Personalize Immunosuppressive Therapy: Preliminary Results from An On-Going, Italian Study - Scalzotto, Elisa; Corradi, Valentina; Salin, Alberto; Caprara, Carlotta; Skoumal, Réka; Neri, Andrea; Cannone, Manuela; Frigo, Annachiara; Chiaramonte, Stefano; Ferrari, Fiorenza; Ronco, Claudio (Journal of Organ Transplantation, 2017)
Single-nucleotide polymorphisms (SNPs) in genes involved in immune responses and in the pharmacokinetics/pharmacodynamics of immunosuppressive drugs influence transplant outcomes of patients receiving the same immunosuppressive therapy. The aim of our preliminary study was to determine the SNPs profiles of ABCB1/MDR-1, UGT1A9, IMPDH2, IL-10 and TNF-α genes associated with acute rejection (AR) events in renal allograft recipients. DNA was extracted from whole blood samples of 220 individuals in 3 experimental groups; Case: 41 kidney transplant patients with AR event(s), Control I: 109 kidney transplant patients without AR event, Control II: 70 healthy blood donors. Acute rejection defined as rapid, unexplained rise in serum creatinine was biopsy-proven. 19 SNPs were analyzed by Sanger Sequencing. Analysis of allele and genotype frequencies and gene-disease association tests were performed. Allele frequencies of healthy persons are in line with ones reported from Europe indicating that the studied population is representative. Statistically significant differences only by the comparison of kidney transplant patients with AR event(s) and healthy individuals are found for rs2032582 and rs1045642 SNPs of ABCB1/MDR1, the latter is also not in Hardy-Weinberg equilibrium in our population. Patients with specific alleles for these SPNs are more prone to have acute rejection events. Certain allele variants of ABCB1/MDR1 by modifying the effectiveness of the drugs may compromise the success of the immunosuppressive therapy and put patients at higher risk to reject the new organ. Therefore screening for these polymorphisms before transplantation would help clinicians to more accurately personalize medications.
Keywords: Single-nucleotide polymorphisms; Kidney Transplant; Acute rejection; ABCB1/MDR-1; UGT1A9; IMPDH2; IL-10; TNF-α